ANALISIS PENGARUH KEBIJAKAN PENGELOLAAN PIUTANG TERHADAP PROFITABILITAS PADA KOPERASI UNIT DESA UNATISA DI DESA ALLANG - Chricela Natalia Joseph (Jurnal Cita Ekonomika, 2017)
The aim of this study was to determine the receivables management policy analysis on the profitability of the Village Unit Cooperative Unatisa in Allang Village. This study performed on Village Unit Cooperative Unatisa in Allang Village. Discussion of the results using; Analysis of receivables turnover, Return On Assets (ROA), the method is simple regression analysis. The results showed that: analysis of receivables management policy for the Village Unit Cooperative Unatisa in Allang Village has decreased every year, it can be seen in the results of the calculation of account receivable turnover, Rasio Profitability in Village Unit Cooperative Unatisa in Allang Village has decreased every year, it can be seen in the results of the calculation of Return On Assets (ROA), and from the results of simple linear based on the results of the proposed research is acceptable, because in accordance with the existing results which prove that the debt management policy has positive influence on the profitability of the Village Unit Cooperative Unatisa in Allang Village.